2014
DOI: 10.1074/jbc.m114.547448
|View full text |Cite
|
Sign up to set email alerts
|

The Human Gene SLC25A29, of Solute Carrier Family 25, Encodes a Mitochondrial Transporter of Basic Amino Acids

Abstract: Background: SLC25A29 encoded by the human SLC25A29 gene was suggested to be a mitochondrial carnitine/acylcarnitine-or ornithine-like transporter. Results: The recombinant, purified SLC25A29 transports arginine, lysine, and to a lesser extent ornithine and histidine but not carnitine and acylcarnitines. Conclusion: SLC25A29 is a mitochondrial transporter for basic amino acids. Significance: Another member of the mitochondrial carrier superfamily responsible for 12 monogenic diseases has been thoroughly charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 56 publications
1
69
0
Order By: Relevance
“…In recent years many of these transporters have been investigated at the molecular and biochemical levels. They transport inorganic anions, amino acids, carboxylic acids, nucleotides, and coenzymes across the inner mitochondrial membrane and in a few cases across other membranes (1,(3)(4)(5). The importance of mitochondrial carriers is demonstrated by their wide distribution in all eukaryotes, their role in numerous metabolic pathways and cell functions, and the identification of several diseases caused by alterations of their genes (1, 2, 6 -8).…”
mentioning
confidence: 99%
“…In recent years many of these transporters have been investigated at the molecular and biochemical levels. They transport inorganic anions, amino acids, carboxylic acids, nucleotides, and coenzymes across the inner mitochondrial membrane and in a few cases across other membranes (1,(3)(4)(5). The importance of mitochondrial carriers is demonstrated by their wide distribution in all eukaryotes, their role in numerous metabolic pathways and cell functions, and the identification of several diseases caused by alterations of their genes (1, 2, 6 -8).…”
mentioning
confidence: 99%
“…Ort1p exchanges ornithine, arginine, and lysine but can also catalyze ornithine/proton exchange, which was also shown to be the case for the purified ornithine carrier from rat liver (Indiveri et al 1999). The human "ornithine carriers" ORC1 (SLC25A15), ORC2 (SLC25A2), and SLC25A29 (Fiermonte et al 2003;Porcelli et al 2014), and the Arabidopsis thaliana carriers BAC1 and BAC2 (Hoyos et al 2003;Palmieri et al 2006b) were identified and characterized using recombinant expression and reconstitution methods; they were shown to have different substrate specificities. In this review, we summarize and discuss the knowledge about these six biochemically characterized MCs that all transport ornithine and related substrates.…”
Section: Xx[k/r]x[k/r] (20-30 Residues) [D/e]gxxxx[w/y/f][k/r]g (Prosmentioning
confidence: 99%
“…The transport characteristics of yeast Ort1p , Arabidopsis BAC1 (Hoyos et al 2003), and BAC2 (Palmieri et al 2006b) as well as of human ORC1, ORC2 (Fiermonte et al 2003), and SLC25A29 (Porcelli et al 2014) have been determined by expressing the proteins in bacteria, purifying the resulting inclusion bodies and reconstituting the MCs into liposomes followed by transport assays. The transport experiments were done by loading the MC-containing proteoliposomes with excess cold internal substrate and initiating substrate exchange by the addition of radioactive external substrate.…”
Section: Xx[k/r]x[k/r] (20-30 Residues) [D/e]gxxxx[w/y/f][k/r]g (Prosmentioning
confidence: 99%
See 1 more Smart Citation
“…Another gene of the same family, SLC25A29, encodes a mitochondrial transporter that was also proposed to vicariate the function of ORNT1 and was named ORNT3 (Camacho and Rioseco-Camacho 2009). However, this protein presents less than 50% of sequence similarity and a recent work showed that SLC25A29 transports preferentially lysine and arginine and to a much lesser extent histidine and ornithine when expressed in phospholipid vesicles (Porcelli et al 2014).…”
Section: Introductionmentioning
confidence: 97%